(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Asthma, a global public health problem, is affecting both developing and developed countries. Bangladesh is one of the asthma prone countries with high concentration of the disease in Mymensingh zone. This study has been conducted to identify the determinants and impact of asthma disease in Mymensingh zone of Bangladesh. Cluster sampling technique is used for sampling 100 asthmatic patients from Mymensingh zone. Different socio-economic and biological information of the asthmatic patients have been collected. Multinomial logistic regression and multivariate logistic regression have been used to find out the determinants and impact of asthma.The result suggests that the likelihood of being in severe asthma is 5.182 times higher if the public rule of smoking is not maintained in work place. Positive impact of access to sunlight and presence of cockroaches, mice or rats in household on reducing asthmatic condition was also revealed in the analyses. The multivariate logistic regression suggests that hypertension and weight change both are significantly influenced by disease status of asthma.This research identifies that along with other determinants smoking in the working places is an important determinant of asthma in Mymensingh zone of Bangladesh. Furthermore, asthma is found to have significant influence on hypertension and weight change which will guide the policy planners and health professionals to address the issues together in systematic fashion. Mymensingh zone being an asthmatic region needs special attention in the national health program. J. Bangladesh Agril. Univ. 16(3): 478–481, December 2018